Patterns of Public Speaking in PAI Teaching At Arriyadh Insan Cendekia Islamic Elementary School, Bekasi City - Roihani, Dini; Suharyat, Yayat; Baharuddin (Proceeding International Conference on Education, 2023)
PAI teaching is the foundation of an education, in order to produce students who have noble character. Whatever the method, as long as the teacher's speech can inspire and influence the thoughts, feelings and actions of students. This study aims to design the use of public speaking in teaching Islamic Religious Education, designing stages of teaching Islamic Religious Education with systematic communication, overcoming obstacles encountered in public speaking in teaching Religious Education. The research method used is qualitative by collecting data through interviews and observation. The subject of this study was the Islamic Islamic Elementary School teacher Arriyadh Insan Cendekia Bekasi City. The results of the study explain that teaching PAI with speaking techniques using Public Speaking can affect the morals and implementation of student worship.PAI teaching is the foundation of an education, in order to produce students who have noble character. Whatever the method, as long as the teacher's speech can inspire and influence the thoughts, feelings and actions of students. This study aims to design the use of public speaking in teaching Islamic Religious Education, designing stages of teaching Islamic Religious Education with systematic communication, overcoming obstacles encountered in public speaking in teaching Religious Education. The research method used is qualitative by collecting data through interviews and observation. The subject of this study was the Islamic Islamic Elementary School teacher Arriyadh Insan Cendekia Bekasi City. The results of the study explain that teaching PAI with speaking techniques using Public Speaking can affect the morals and implementation of student worship